Life in a longhouse village - Kalman, Bobbie (New York : Crabtree Pub. Co., 2001)
This book introduces children to the traditional daily life of the Native nations who lived in longhouses and shared a common way of life.
Includes index.
NC1020L
Keywords: Iroquois Indians -- Juvenile literature; Longhouses -- Juvenile literature; Indians of North America -- Northeastern States; Dwellings